AB0786 Systematic review of measurement properties of patient reported outcome measures in psoriatic arthritis: a grappa-omeract initiative. (15th June 2017) - Højgaard, P; Klokker, L; Orbai, A-M; Holmsted, K; Bartels, EM; Leung, YY; Goel, N; Wit, M de; Gladman, D; Mease, P; Dreyer, L; Kristensen, LE; et al.
Abstract : Background: An updated psoriatic arthritis (PsA) core domain set (COS) for randomized controlled trials (RCTs) was endorsed at the Outcome Measures in Rheumatology (OMERACT) meeting in 2016 and reflects the patient and physician perspectives.[1] Objectives: To synthesise the evidence on measurement properties of Patient Reported Outcome Measures (PROMs) in PsA in order to contribute to the development of a PsA core outcome measurement set (COMS) for RCTs adhering to the OMERACT filter 2.0 Framework.[2] Methods: A systematic literature search was performed in EMBASE, MEDLINE and PsycINFO to identify studies published in English on PROM measurement properties in PsA. Two independent reviewers rated the quality of studies according to COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines, [3] extracted data on measurement properties and performed a qualitative evidence synthesis. Results: Of 4703 identified references, 162 were read in full-text and 44 included in the systematic review (SR). Thirty-nine instruments, consisting of one or more scales, were analysed. PROMs measuring core set domains with at least fair quality evidence for good validity and reliability (and without evidence for inadequate measurement properties) were: Stockerau Activity Score for PsA (German) for the Musculoskeletal Disease Activity domain; the Psoriatic Symptom Inventory for Skin Disease Activity ; the 36-Item Short Form Health Survey Physical Function scale and to a lesser extent the Health Assessment Questionnaire Disability Index and Bath Ankylosing Spondylitis Functional Index for Physical Function ; the Psoriatic Arthritis Quality of Life Questionnaire, the Psoriatic Arthritis Impact of Disease questionnaire and VITACORA-19 (Spanish) for Health related Quality of Life/Life Impact; the Functional Assessment of Chronic Illness Therapy-Fatigue Scale for Fatigue, and the Social Role Participation Questionnaire for Participation . Evidence for content validity was lacking for most of these PROMs. Conclusions: At least one PROM with some evidence for good validity and reliability was available for five out of eight inner circle domains of the PsA COS. Lack of content validity evidence constitutes a critical barrier for application to the PsA COS per the OMERACT Filter 2.0 Instrument Selection Algorithm [2]. This SR serves as a guide for additional research to increase knowledge of PROM measurement properties in PsA followed by stakeholder consensus for developing a PsA COMS. PROSPERO:CRD42016032546 References: Orbai AM, de WM, Mease P et al. International patient and physician consensus on a psoriatic arthritis core outcome set for clinical trials. Ann Rheum Dis 2016. doi: 10.1136. Martin Boers, John Richard Kirwan, Peter Tugwell et al. The OMERACT handbook. Updated May 2016, http://www.omeract.org . Terwee CB, Mokkink LB, Knol DL et al. Rating the methodological quality in systematic reviews of studies on measurement properties: a scoring system for the COSMIN checklist. Qual Life Res 2012;21:651–7. Disclosure of Interest: P. Højgaard Speakers bureau: Received speaking fees once from Celgene and UCB not related to the current work, L. Klokker: None declared, A.-M. Orbai: None declared, K. Holmsted: None declared, E. Bartels: None declared, Y. Y. Leung: None declared, N. Goel Employee of: QuintilesIMS, M. de Wit: None declared, D. Gladman: None declared, P. Mease: None declared, L. Dreyer: None declared, L. Kristensen: None declared, O. FitzGerald: None declared, W. Tillett: None declared, L. Gossec: None declared, P. Helliwell: None declared, V. Strand: None declared, A. Ogdie: None declared, C. Terwee: None declared, R. Christensen: None declared